THE CONTRIBUTION OF WENGERIAN SCIENTIST HERMAN VAMBER TO UZBEK PEOLOGY - Rahmatov Yuldosh Gaybullaevich (Journals Park Publishing, 2022)
The article talks about Hungarian scientist Herman Vambery's trip to Central Asia and his attitude to Uzbek folklore, especially folk proverbs. It is also considered that the scientist should collect Uzbek proverbs, publish them, and translate them into German. How H. Vamberi interpreted the content of Uzbek folk proverbs is expressed.
Keywords: conquest, tourist, spy